2014
DOI: 10.3109/01443615.2014.960823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise on premenstrual symptoms, haematological and hormonal parameters in young women

Abstract: The objective of this study was to investigate the effect of aerobic exercise on premenstrual symptoms, haematological and hormonal parameters in young women. A total of 30 participants aged 16-20 years and complaining of premenstrual syndrome (PMS) were randomly assigned into two groups: a control group received vitamin B6 and Ca supplements once daily and a study group received the same medical treatment and participated in treadmill training three times per week for 3 months. A premenstrual syndrome questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 28 publications
(33 reference statements)
2
41
2
Order By: Relevance
“…Some studies have shown that increasing physical activity improves severity of symptoms within 3 months of starting an exercise regimen [16,17,19]. Despite the potential biological connections between physical activity and endorphin levels [5,8], decreased levels of sex hormones [9,10], improvement of oxygen in muscles [9], and a reduction of cortisol levels [9], studies remain largely inconsistent on linking physical activity and reduced premenstrual symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that increasing physical activity improves severity of symptoms within 3 months of starting an exercise regimen [16,17,19]. Despite the potential biological connections between physical activity and endorphin levels [5,8], decreased levels of sex hormones [9,10], improvement of oxygen in muscles [9], and a reduction of cortisol levels [9], studies remain largely inconsistent on linking physical activity and reduced premenstrual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest a protective effect [8,1119], one showed no association [20], and two studies found higher levels of premenstrual symptoms among women who exercised more compared to those exercising less or not at all [21,22]. Multiple factors could contribute to the differences in findings between studies.…”
Section: Introductionmentioning
confidence: 99%
“…There was also a significant decrease in prolactin, oestradiol and progesterone levels. In conclusion, aerobic exercise increases haemoglobin, haematocrit, red cell count and platelet count, and decreases levels of prolactin, oestradiol and progesterone, resulting in improvement of fatigue, impaired concentration, confusion and most premenstrual symptoms [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Initially, Sample size According to El-Lithy’s study [15], 30 people in each group were estimated, with Considering sample loss, 35 people were estimated in each group. At first, randomly and according to the table, two hostels were randomly selected and in order to avoid any interference in the sampling, a dormitory was considered as the control group and one was considered as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…A severe form of this syndrome is called premenstrual dysphoric disorder [22, 23]. Clinical manifestations of premenstrual syndrome include fatigue, impaired concentration [24, 25], confusion [24], headache [26], and depression [27]. These clinical features are also observed in toxoplasmosis.…”
Section: Introductionmentioning
confidence: 99%